PEMIDANAAN TERHADAP PELAKU PENYALAHGUNAAN NARKOTIKA SECARA BERSAMA UNTUK DIRI SENDIRI - Bella Oktavia Hardimanto; Dhany Rahmawan (Fakultas Hukum Universitas Trisakti, 2022)
The large number of narcotics abusers are imprisoned, causing prisons to become overcapacity. In addition, narcotics abusers should receive rehabilitation sentences because it is stated in the Narcotics Law, such as the case of Muhammad Wahyudi, who was legally guilty of committing Narcotics Abuse in Group I for himself. The research study is based on court decision number: 50/ Pid. Sus/2021/PN. Ktb. The research’s problems: are the actions of the defendant in Court Decision number: 50/Pid.Sus/2021/PN.Ktb in accordance with the provisions of the applicable laws? The research conducted in normative and descriptive analytical legal research, the data and the data sources used in this research are statutory regulations, jurisprudence and legal doctrines that relevant to the case. The data are analyzed qualitatively and the conclusions are drawn using deductive understanding method. The conclusion from this research is that the abusers must receive punishment in the form of rehabilitation, not imprisonment, because it is guaranteed by the narcotics law and the judges must consider and pay attention to the authority and the obligations of the judge regulated in the narcotics law which are mandatory to provide rehabilitation.